1999
DOI: 10.1088/0022-3727/32/10/303
|View full text |Cite
|
Sign up to set email alerts
|

On the free layer reversal mechanism of FeMn-biased spin-valves with parallel anisotropy

Abstract: Transmission electron microscopy has been used to investigate the 'free' layer reversal mechanism of a range of FeMn-biased spin-valves with parallel anisotropy. Fresnel imaging enabled three modes of reversal to be directly observed for different in-plane applied field orientations and interlayer coupling strengths. Low-angle diffraction has provided some quantitative information on the level of dispersion involved in the reversals. Comparison with a modified Stoner-Wohlfarth coherent rotation model is made a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
2
5
0
Order By: Relevance
“…In practice, it has been shown that reversal often occurs at slightly lower fields and involves the formation of domains. 22 Nonetheless, the orientation of magnetization before the formation of domains and after their annihilation is similar to the orientations before and after the jump predicted in the SW model. Domain walls normally form in an orientation that ensures that the perpendicular component of magnetization is the same on either side of a wall.…”
Section: Difference In Domain-wall Orientation On the Outward Andsupporting
confidence: 75%
See 1 more Smart Citation
“…In practice, it has been shown that reversal often occurs at slightly lower fields and involves the formation of domains. 22 Nonetheless, the orientation of magnetization before the formation of domains and after their annihilation is similar to the orientations before and after the jump predicted in the SW model. Domain walls normally form in an orientation that ensures that the perpendicular component of magnetization is the same on either side of a wall.…”
Section: Difference In Domain-wall Orientation On the Outward Andsupporting
confidence: 75%
“…22 In particular, study of how the total energy varies as a function of magnetization orientation for a fixed orientation of applied field allows predictions to be made of the circumstances under which domain walls are likely to form and the orientation they are likely to assume. In the SW model, irreversible jumps in magnetization occur on the disappearance of an energy barrier separating a local energy minimum from a global energy minimum.…”
Section: Difference In Domain-wall Orientation On the Outward Andmentioning
confidence: 99%
“…10 This article presents a study of the domain patterns during the magnetization reversal in exchange-biased Co/NiO bilayers, for different angles between the applied magnetic field and the exchange biasing axis. In some way, our measurements are similar to what has been done for the free ferromagnetic layer in spin-valve structures, 4 with a corresponding theoretical model. 11 The influence of the interface between the ferromagnet and antiferromagnet, however, can only be studied via the reversal of the pinned layer.…”
supporting
confidence: 77%
“…A comparison of experimental results for these configurations was performed, e.g., in [4]. It has been revealed [15] that the maximum mag netoresistive sensitivity (%/Oe) at the minimum hys teresis of the free layer is characteristic of the spin valve corresponding to the nearly parallel configuration. As was shown by magnetooptical investigations [16], the physical cause responsible for the decrease in the hys teresis of the free layer depending on the geometrical factors is the change in the mechanism of magnetiza tion reversal of this layer.…”
Section: Introductionmentioning
confidence: 99%